Equity Practices of Teaching Science at Secondary Level - Gautam, Tikaram (KMC Research Journal, 2020)
The main objectives of this study is to explore the equity practices in science classroom. Implementation of equity provision in science classroom is very important. Equity means ensuring the needs of the students according to their necessities. It focuses on individual teaching. All students are different and having the specific capacity and capacity of learning and teacher should facilitate them all according to their ability and they should have rights to equal access in resources and other extra supports for their improvement and also should have the equality in achievement. To reveal such practices in learning science researcher used phenomenological study. Two secondary science teachers were selected using purposive and convenient sampling method. The in-depth interview was taken for data collection two times to saturate the data. Collected data were analyzed using thematic analysis. Practices of equity provision were found weaker. Teacher were found little bit concerned about the equity in pedagogy but it was limited only to sitting arrangement and group division. They could not provide the adequate concern on homework checkup, and individual teaching. And they were found less concerned about the equity in achievement. Hence, it is necessary to organize workshops and training on professional development issues to implementation of equity provision; equity in access, equity in process as well as equity achievement in the science classroom.